Does decision-making style predict managers' entrepreneurial intentions? - Besnik A. Krasniqi; Gentrit Berisha; Justina Shiroka-Pula (Journal of Global Entrepreneurship Research, 2019)
The purpose of this paper is to investigate whether the way managers make decisions (their decision-making style-DMS) predicts their entrepreneurial intentions (EI), a research subject that has been largely ignored in the literature. Developing an understanding of entrepreneurial intention factors that attract managers to entrepreneurship is indispensable for organizations. A sample of 230 managers of companies based in Kosovo was asked to take the entrepreneurial intention questionnaire and the General Decision-Making Style (GDMS) questionnaire. Bridging two strands of literature on decision-making and entrepreneurial intention and using the Structural Equation Model (SEM), it is concluded that spontaneous and intuitive styles predict managers' entrepreneurial intentions. Considering the limitations of this single-country study, the implications for theory and policy are discussed.
Keywords: 650; Decision-making style; Cognitive style; Intuitive; Spontaneous; Entrepreneurial intention